Association of Polymorphisms in the Human IL4 and IL5 Genes With Atopic Bronchial Asthma and Severity of the Disease. Issue 3 (2003) - Freidin, Maxim B.; Kobyakova, Olga S.; Ogorodova, Ludmila M.; Puzyrev, Valery P.
Abstract : Two polymorphisms in the IL4 (G/C 3′-UTR) and IL5 (C-703T) genes were studied in a sample of families whose probands had atopic bronchial asthma (BA) (66 families, n = 183) and in a group of non-cognate individuals with the severe form of the disease (n = 34). The samples were collected from the Russian population in the city of Tomsk (Russia). Using the transmission/disequilibrium test (TDT), a significant association of allele C-703 IL5 with BA was established (TDT = 4.923, p = 0.007 ± 0.0007). The analysis of 40 individuals with mild asthma and 49 patients with the severe form of the disease revealed a negative association of genotype GG IL4 (OR = 0.39, 95% CI = 0.15−0.99, p = 0.035), and also a trend towards a positive association of the GC IL4 genotype (OR = 2.52, 95% CI = 0.98−6.57, p = 0.052) with mild BA. There was a concordance of the clinical classification of BA severity with the 'genotype' (McNemar'sχ 2 test with continuity correction constituted 0.03, d.f. = 1, p = 0.859). These results suggest that polymorphisms in the IL4 and IL5 genes contribute to the susceptibility to atopic BA and could determine the clinical course of the disease.